Discovery Learning Model to Improve the Quality of Student Learning Post Covid 19 Pandemics - Saputra, Rahmat; Utami, Fitria Budi; Kasih, Delina (Universitas Nahdlatul Ulama Blitar, 2024)
This study aims to analyze the post-pandemic learning process using the Discovery Learning method. The population of this study was all class A students of the Industrial Engineering study program in the fourth semester of Muhammadyah University A.R. Fachruddin, numbering approximately 26 people. Determination of the sample in this study is the saturated sample method so that the number of samples is the same as the number of populations, namely as many as 26 samples. This research is quasi-experimental. This research was conducted using an online discovery learning model. Based on the results of data analysis, it can be concluded that there are differences in quality between learning using the Discovery Learning method and without Discovery Learning. According to the results of the analysis, the Discovery Learning learning method is of higher quality than learning without using the Discovery Learning method.